Assessment of different types of anesthetic agents in oreochromis niloticus - Lim Wei Li (2022)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT 5436 – Research Project. Fish is also one of the living organisms that display neuroendocrine and physiologic stress responses toward environment. There are many anesthetics, sedatives and also analgesic drugs that are available and used in other vertebrates to reduce stress in fish, reduce handling trauma, restrict movement and physiologic changes in response to nociceptive stimuli and also euthanasia. This experiment aims to determine the minimum effective dose of 2- Phenoxyethanol, clove oil, Nika Transmore and MS-222 in adult Nile tilapia. Fishes were immersed in three different doses of each anesthetic and the minimal dose that produce stage 3 anestheisa within 10 minutes, maintain stage 3 anesthesia for 3 minutes was considered the optimal dose. As a result, the optimal dose for 2-Phenoxyethanol, clove oil, Nika Transmore and MS-222 in average 250g Nile Tilapia housed at 24°C were 300, 20, 75 and 90 ppm, respectively. Keywords: Anesthetics; 2-Phenoxyethanol; Clove oil; Nika Transmore; MS-222